2009
DOI: 10.1080/02791072.2009.10400538
|View full text |Cite
|
Sign up to set email alerts
|

Modified Therapeutic Communities and Adherence to Traditional Elements

Abstract: Traditional therapeutic communities (TCs) are characterized by confrontational group therapy, treatment phases, a tenure-based resident hierarchy, and long-term residential care. Many TCs have modified the structure and intensity of the traditional model, tailored services for specific client populations, and hired more professionally trained staff. This study examines the extent to which modified TCs are able to retain the underlying core technology of the TC. Using data from a nationally representative sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…For a total of 380 self-identified TCs they concluded that certain modifications to the traditional TC model are possible without losing the TC model's core technology. However, modifications of the structure or to the intensity of the TC programming did have a significant impact on adherence to the TCs' core characteristics (Dye et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For a total of 380 self-identified TCs they concluded that certain modifications to the traditional TC model are possible without losing the TC model's core technology. However, modifications of the structure or to the intensity of the TC programming did have a significant impact on adherence to the TCs' core characteristics (Dye et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…North-American studies have shown that, although some significant variations in adherence to the 'community as method' elements of the traditional TC model could be found, all TCs, traditional or modified, still remain true to the basic elements outlined in De Leon's classic TC model (Dye et al, 2009;Melnick & De Leon, 1999). Considering previous findings, we expect that the European traditional TCs will demonstrate a higher degree of adherence to the key characteristics of a traditional TC model than the European modified TCs, but that overall they will be more alike than different.…”
Section: Introductionmentioning
confidence: 99%
“…Full descriptions regarding how these samples were constructed in [2002][2003][2004] have been published (Dye, Ducharme, Johnson, Knudsen, & Roman, 2009;Knudsen, Ducharme, & Roman, 2007). Briefly, the strategy relied on random sampling of U.S. counties from 10 population-based strata, identification of all treatment organizations in these counties using published directories, random sampling of organizations, and telephone screening.…”
Section: Samples and Data Collectionmentioning
confidence: 99%
“…The term TC designates both a type of residential or semi-residential service that provides psychosocial rehabilitation for persons with diagnoses of mental illness [12][13][14] or drug addiction problems [15,16] and the therapeutic method employed therein [17,18]. The TC method emphasises prolonged interaction between staff and clients (the so-called "living-learning experience" [12] or "community as method" [19,20]), usually over a period of several months [21], in joint work, learning and leisure activities. Staff-led group meetings take place on a weekly basis and are occupied to a significant extent by clients' reports of their recent activities and experiences [22,23].…”
Section: Therapeutic Community Meetingsmentioning
confidence: 99%
“…After a negative answer (line 3), Diana both displays difficulty in recalling what she did and overtly states that she does not remember (lines 6, 14, 17-18) [37]. Roberto produces a KD, which treats Diana's response as contradicting previous knowledge (lines [21][22] that she got "mad" (the KD is prefaced with the words "except that", which set a contrast between this information and the client's claim that she does not remember and, hence, that there is nothing that she can report). After a 2.3 seconds silence and overlapping Diana's hard-to-hear response at line 24 (in which she might be downplaying the significance of the episode by saying that it is the "same" kind of thing that tends to happen to her), Roberto overtly challenges the idea that Diana does not remember (lines [25][26][27][28][29][30].…”
Section: -22)mentioning
confidence: 99%